(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article deals with the issues of marketing tools for entering foreign markets. The success of entering these markets is ensured by a comprehensive strategic analysis of the international environment, its main features and enabling factors. Of great importance is also a reasonable choice of optimal strategies for the foreign economic activity of enterprises, entering foreign markets and their subsequent development. For the whole complex of measures for the strategic planning of enterprises entering foreign markets, multivariate and phased road mapping will be required.